FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN JAMBAN KELUARGA DALAM PROGRAM PAMSIMAS DI XIII KOTO KAMPAR - Lestari, Rizki Rahmawati; Gustiana, Etri (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Based on the Johannesburg declaration that by 2023 half of the world's population must have access to basic sanitation (latrine). This determination emphasizes the importance of programs to increase public awareness of the need to own and use latrines. The aim of this research is to determine the factors related to the use of family latrines in the Pamsimas program in the XIII Koto Kampar work area in 2023. This research uses a quantitative analytical design with a cross sectional approach. The research population is all 2730 heads of families (KK) in XII Koto Kampar. KK with a sample of 97 KK taken using systematic random sampling. The measuring tool in this research is a questionnaire. The data analysis used was Univariate and Bivariate, with the chi-square test. The results of statistical tests can be concluded that there is no significant relationship between the level of education and latrine use, p value 0.080 < 0.05, there is a significant relationship between the level of knowledge, attitudes and roles of health workers and latrine use (p value = 0.008, p value = 0.049, p value = 0.009. This research recommends the importance of providing sanitation information or counseling to the community about always using latrines, providing model latrines that meet health requirements to encourage people to always use latrines after the PAMSIMAS program is completed with the help of Health Officers.